Removal of Co(II) and Cr(II) from Aqueous Solution Using Ferronia elefuntum Fruit Shell Substrate - Gharde, B.D.; Gholse, S.B.; Patil, P.V. (Asian Journal of Chemistry, 2016)
Ferronia elefuntum fruit shell substrate was found to have good sorption capacity for cobalt(II) and chromium(VI). Studies indicate that the sorption of Co2+ and Cr6+ increases with the increase in pH value and a contact time of 60 min was found to be optimum. The effect of concentration shows that fruit shell substrate can remove Co2+ and Cr6+ ions from water.